To solve the equation 4(2y-6) + 3 = 11, we can start by simplifying the left side of the equation.
4(2y-6) + 3 = 11
First distribute the 4 to every term inside the parentheses:
8y - 24 + 3 = 11
Combine like terms:
8y - 21 = 11
Now, isolate the variable y by adding 21 to both sides of the equation:
8y - 21 + 21 = 11 + 21
8y = 32
Finally, divide both sides of the equation by 8 to solve for y:
8y/8 = 32/8
y = 4
Therefore, the solution to the equation is y = 4.
Solve the equation
4(2y-6)+3 = 11
Y=3
Y=-3
Y=4
Y=5
1 answer